Policy analysis in the field of rare diseases in China: a combined study of content analysis and Bibliometrics analysis - Li, Xiaotao; Wu, Lan; Yu, Lina; He, Youqin; Wang, Min; Mu, Yan (Frontiers in Medicine, 2023)
The Chinese government has made significant strides in addressing the needs of individuals affected by rare diseases in recent years. This paper presents a mixed-methods analysis of national rare disease policies in China from 2009 to 2022. A two-dimensional analytical framework, which encompasses policy tools and policy themes, is introduced to provide a comprehensive overview of these policies. Drawing on the policy tools theory proposed by Rothwell and Zegveld, this paper evaluates the tools utilized in rare disease policies. Co-word analyses and network analyses were employed to identify key themes in rare disease policies and collaboration among government departments. The rare disease policy landscape in China is undergoing rapid growth, with an increasing number of government departments involved in policy formulation. However, further collaboration between departments is needed to strengthen these policies. Environment-based and supply-based tools are preferred in rare disease policies. The policy themes can be grouped into four categories. (1) Registration, Approval and Supply of Rare Disease Drugs. (2) Construction of Diagnosis and Treatment System for Rare Diseases. (3) Development and Genericization of Rare Disease Drugs. (4) Social Security for Patients with Rare Diseases. This study provides valuable insights into the current state of rare disease policies in China and offers suggestions for policy improvement. It serves as a foundation for further understanding of this important issue and its impact on public health.